ASSOCIATIONS AMONG LEVEL OF EDUCATION AND INCOME ON SEPARATION BEHAVIOR'S OF RECYCLABLE MATERIALS AT ILHA SOLTEIRA–SP - PEREIRA, Gracely Ortega Tavares; BRASILEIRO, Luzenira Alves; SALGADO, Douglas D'Alessandro; PEREIRA, Danilo Florentino (Revista Brasileira de Engenharia de Biossistemas, 2012)
The management of solid waste - MSW generates impacts on the welfare of the population, especially those working with the collection, separation and marketing of recyclable materials. This study found associations between income, education and neighborhood residents of Single Island - SP, with the behavior of separation of recyclable materials. We interviewed 216 residents in different homes throughout the urban area, corresponding to a confidence level of 99.6%. It was found that the proportion of the population more educated and better paid significantly less and less separated range of recyclable materials due to lack of motivation and lack of confidence in municipal management. It is hoped that these results conducive to the Municipality to correct flaws in the management of RSD and plan specific actions for each portion of the population